COMPARISON OF RICE FARMER'S INCOME (ORYZA SATIFA L.) BETWEEN MEMBERS AND NON-MEMBERS OF FARMER GROUPS (CASE STUDY OF NAGARI SALAYO, KUBUNG DISTRICT, SOLOK REGENCY, WEST SUMATRA PROVINCE - Alfin Chairil; Jumatri Yusri; Deby Kurnia (Indonesian Journal of Agricultural Economics, 2022)
This study aims to examine the comparison of the income of rice farmers between members of farmer groups and non-members of farmer groups in Nagari Salayo, Kubung District, Solok Regency, West Sumatra. The analytical method used is descriptive analysis, farming analysis and the average difference test of two independent samples (Independent sample t-test). The number of samples consisted of 35 rice farmers who were members of the farmer group and 35 rice farmers who were not members of the farmer group. The results showed that the farming of farmers belonging to farmer groups was more profitable than farmers who were not members of farmer groups, it could be seen from the value of the R/C ratio over the total cost of farmers belonging to farmer groups of 2.28, greater than the R/C ratio obtained by non-group members, namely of 2.08. Thus, farmer group membership has an effect on increasing farm income of rice farmers